FOSTERING INNOVATION THROUGH TRAINING TRANSFER AND COLLABORATIVE WORK ENVIRONMENTS: A MEDIATING PATHWAY TO ENHANCED PUBLIC SECTOR PERFORMANCE IN AGRICULTURAL TECHNICAL UNITS - Deddy Sumarna; Irsan Tricahyadinata; Herry Ramadhani (RADJA PUBLIKA, 2025)
Background: Public-sector agricultural technical units in East Kalimantan face food security challenges owing to crop losses and limited innovation, demanding improved employee performance through training transfers and collaborative work environments. Objectives: This study examines the direct effects of training transfer and collaborative work environment on employee innovation and performance, as well as the mediating role of innovation in the relationship between the Technical Implementation Unit of the Food Crops and Horticulture Protection Agency (UPTD). Methods: A quantitative approach with Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) was used, involving 79 UPTD employees. Data were collected through a Likert scale-based questionnaire and analyzed using SmartPLS 4. Results: Training transfer (β = 0.311) and collaborative work environment (β = 0.545) had significant effects on innovation, which mediated the relationship with employee performance (β = 0.691; β = 0.721). The model explains 68.5% of the variance in innovation and 75.4% of the variance in performance. Implications: This study extends the theory of training transfer and collaboration in the agricultural public sector. Practically, it recommends technical training and a collaborative culture to improve performance and food security.